Deconstructing Masculinity: K–Pop's Effect in Shaping a New Representation of Men - Tengku Walisyah; Ahmad Tamrin Sikumbang; Erwan Efendi (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines how K-Pop culture influences the construction and deconstruction of male masculinity in Indonesia in complex social, cultural, and religious contexts. Using a virtual ethnography approach and social media sentiment analysis, this study reveals that representations of masculinity in K-Pop culture—which are gentle, aesthetic, and androgynous—challenge traditional Indonesian masculinity norms that emphasize assertiveness, dominance, and emotional restraint. K-Pop idols as cosmetic brand ambassadors introduced a new form of masculine expression that was more inclusive, but triggered resistance from conservative Islamic norms and values. The novelty of this research lies in the integration of visual analysis, online discourse, and religious perspectives in explaining the negotiation of gender identity in the digital era. The findings show that masculinity is now a tug-of-war between global and local values. Social media serves as a cultural mediation arena where new masculine images can be negotiated, tested, and maintained. This study confirms that K-Pop is influential as an ideological agent in destabilizing and reformulating the boundaries of male identity in contemporary Indonesian society.